Motivasi Belajar dan Regulasi Diri Mahasiswa Selama Pandemi Covid-19 - Sri Hardianti Sartika (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: During the Covid-19 Pandemic, learning motivation and self-regulation were identified as factors that influenced college student to involving in learn process. The research focus is to explain the objective conditions of learning motivation and self-regulation of college student during the pandemic. The reserach is a quantitative study with an interpretive approach involving 88 college student in 3rd semester in Department of Economic Education at Siliwangi University, as participants. The data was collected by means of a survey in the form of a questionnaire that adopted the measuring instrument of learning motivation and self-regulation developed by Velayutham et al. The survey was carried out by distributing questionnaires in the form of googleform so that it was easily accessed by students. Data analysis uses the calculation of the percentage of each indicator and analyzes it in depth. The finding indicate that the condition of student learning motivation during the Covid-19 pandemic as measured by 3 indicators learning in goal orientation, task value and self-efficacy are in the excellent category with a score of 83%. Self-regulation of college student in learning during the Covid-19 pandemic is in the excellent category or with a score of 81%. The excellent categories of learning motivation and self-regulation describe that college students are able to adapt in pandemic emergency online learning. Abstrak: Pada masa Pandemi Covid-19, motivasi belajar dan regulasi diri diidentifikasi sebagai faktor yang mempengaruhi keterlibatan mahasiswa dalam pembelajaran. Fokus penelitian ini menjelaskan kondisi objektif motivasi belajar dan regulasi diri mahasiswa selama masa pandemi. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan interpretative yang melibatkan 88 orang mahasiswa semester 3 pada Jurusan Pendidikan Ekonomi di Universitas Siliwangi, sebagai partisipan. Pengumpulan data dilakukan dengan cara survey berupa kuesioner yang mengadopsi instrumen pengukuran motivasi belajar dan regulasi diri yang dikembangkan oleh Velayutham dkk. Survey dilakukan dengan menyebarkan kuesioner berupa googleform agar mudah diakses oleh mahasiswa. Analisis data menggunakan perhitungan presentase dari setiap indikator dan menganalisisnya secara mendalam. Temuan ini menunjukan bahwa kondisi motivasi belajar mahasiswa selama pandemi Covid-19 yang diukur dengan tiga indikator yaitu, orientasi pada tujuan, nilai tugas dan efikasi diri termasuk kategori sangat tinggi dengan skor 83%. Regulasi diri mahasiswa dalam pembelajaran selama masa pandemi Covid-19 tergolong pada kategori sangat tinggi atau dengan skor 81%. Kategori motivasi belajar dan regulasi diri yang sangat tinggi tersebut menggambarkan bahwa mahasiswa mampu berdaptasi pada pembelajaran online darurat selama masa pandemi ini.